Natural and anthropogenic sterols inputs in surface sediments of Patos Lagoon, Brazil - Martins,César de Castro (2007)
The Patos Lagoon, the largest coastal lagoon in the world, has long been receiving considerable anthropogenic input resulting from urban, rural and industrial activities. Thus, sewage contamination possibly originating from the more than 2 million inhabitants living within its drainage basin is examined in this study. Sediment samples collected from various points along the Lagoon were extracted, purified and analysed by GC-MS. Ten different sterols and ketones, including coprostanol and epicoprostanol, were identified and quantified. The highest coprostanol concentration was found near Porto Alegre City (1,423 ng g-1 dry wt.), whilst most sediment levels ranged between < DOL and 91.78 ng g-1. The highest concentrations were found at those three sites located closest to domestic outfalls though levels tended to decrease with distance from the sources. The 5beta/(5beta+5alpha) isomeric ratios indicated sewage-contaminated sediments near Porto Alegre City, while the epicoprostanol/coprostanol ratio showed values characteristic of untreated sewage input.